How to reduce a risk of venous thromboembolism while taking combined oral contraceptives - V. O. Bitsadze; J. Kh. Khizroeva; A. G. Solopova; M. V. Kvaratskheliia; D. Yu. Zabolotnaya; Z. Xiaoxia; M. V. Tretyakova; V. I. Tsibizova; N. R. Gashimova; K. N. Grigoreva; M. A. Gileva; A. S. Shkoda; et al. (IRBIS LLC, 2023)
The review presents data on the evolution of combined oral contraceptives (COCs), related most frequent and dangerous side effects including venous thromboembolism (VTE). The issue of VTE upon administration of COCs is highlighted, and the risks of such complication in patients receiving hormonal contraception are determined. The issues of the basic demands of women choosing COCs are considered as well as current opportunities to meet such requests by using novel drug groups with a high profile of efficacy and safety. Particular cases of optimal COCs choice for patients with specific comorbidities such as obesity, hirsutism, seborrhea, alopecia, acne, polycystic ovary syndrome (PCOS), fibrocystic mastopathy, endometriosis as well as in case of gynecological surgical interventions are analyzed. The options of contraceptive therapy are proposed by taking into account individual female wishes (lack of weight gain, decreased libido, etc.).